Comparación del efecto hipolipemiante de la emulsión de aceite de Sacha Inchi/galactomananos con la Simvastatina en diabéticos tipo 2 con dislipoproteinemia - Garmendia, Fausto (2020)
Objectives: To compare the hypolipemic effect of Sacha Inchi/galactomannan´s emulsion (SIE) with Simvastatin (SVT) in diabetics type 2 (DM2) with dislipoproteinemia. Methodology: A doble- blind, randomized, comparative-controlled study was performed. A total of 41 DM2 patients with dislipoproteinemia, both genders, 40 to 70 years old were included. At random, group 1 received SVT 20 mg + placebo emulsion (n=20) and group 2 received 10 ml SIE (sacha inchi, Plukenetia huayllabambana variety, conteining 2g omega-3 fatty acids + 0.03 g de galactomannans from de Tara gum, Caesalpinia spinosa ) + placebo pill (n=21) during 4 months. At fasting total cholesterol (TC), HDL cholesterol (cHDL), triglycerides (Tg), glucose (G), glicosilated hemoglobin (HbA1c), creatinine, trasaminases and TSH were measured by conventional methods, insulin by immunoluminiscence at the begining and every month during 4 months; VLDL, LDL, Non-HDL cholesterol and HOMA coefficient were calculated. Results: At the end of 4 months a significant decrease of TC, Tg, VLDL, LDL and Non-HDL and an increase of cHDL were observed in both groups. Glucose raised 32,7% with SVT and decreased 13% with SIE, p 0,015. The Tg and VLDL decrease and HDL increase was similar en both groups. A higher significant lowering effect of TC, LDL and Non-HDL was observed with SVT than with SIE. Conclusions: Sacha Inchi´s/galactomannans emulsion decreased Tg and VLDL and increased HDL similarly than SVT, being a good alternative for the treatment of dislipoproteinemia in DM2.